(851) إدارة وتنظيم المؤسسات العامة في ج.ع.م- Administration and Organization of Public Enterprises in U.A.R - إسماعيل، يسري خضر (معهد التخطيط القومى, 2026)
ملخص تُعدّ هذه المذكرة البحثية دراسةً أكاديميةً متخصصةً تتناول بالتحليل والدراسة المنهجية واقع إدارة وتنظيم المؤسسات العامة المشرفة في إطار القطاع العام المصري. وقد انطلقت المذكرة من تأطير مفهومي دقيق للمؤسسة العامة بوصفها منظماتٍ عامةً تنشأ لإدارة أوجه النشاط الاقتصادي في الدولة، وتخضع لرقابة أجهزتها المختلفة، مميزةً إياها عن المصالح الحكومية والهيئات العامة من حيث الاستقلالية والشخصية الاعتبارية ومرونة الإدارة. وتناولت الدراسة بالتفصيل مجالات نشاط المؤسسات العامة،، مصنّفةً إياها إلى ثلاثة أنواع رئيسية: مؤسسات تقوم بالتنمية الشاملة لجميع فروع النشاط الاقتصادي، ومؤسسات تختص بتنمية قطاع واحد، ومؤسسات تقتصر على تنمية أحد فروع النشاط النوعي، مستشهدةً بتجارب دولية ناجحة كمؤسسة كورفو التشيلية للإنتاج ومؤسسة سومر بنك التركية. وفيما يخص الجانب الإداري، استعرضت المذكرة أسس الإدارة العلمية وأبرز تعريفاتها، كما اشارت الى خمس وظائف جوهرية للإدارة الفعّالة في المؤسسات العامة هي: التخطيط، والتنظيم، والتجهيز البشري، والتنسيق، والرقابة. كما حدّدت ثلاث وظائف محورية تُناط بالمؤسسات العامة المشرفة على وجه التحديد، وهي: التخطيط والتنسيق، والرقابة على التنفيذ، وتقديم المشورة والخبرة الفنية للوحدات التابعة لها. وفي إطار التنظيم الإداري، اقترح الباحث هيكلاً تنظيمياً وظيفياً استشارياً متكاملاً من ثماني إدارات متخصصة تشمل: إدارة المشروعات، وإدارة البحوث والتقييم، وإدارة التخطيط والمتابعة، وإدارة الشؤون المالية والإدارية، وإدارة مراقبة الحسابات، وإدارة الشؤون القانونية، وإدارة العلاقات العامة، وإدارة شؤون مجلس الإدارة، مع توضيح اختصاصات كل منها بدقة وتفصيل. وقد خلصت الدراسة إلى أن نجاح المؤسسات العامة مرهون بالاستقرار التنظيمي وتطبيق قواعد الإدارة العلمية تطبيقاً سليماً بعيداً عن التغييرات التشريعية المتكررة التي عانت منها هذه المؤسسات منذ إنشائها عام 1957 This research constitutes a specialized academic study that systematically examines the administration and organizational structure of public supervisory enterprises within Egypt's public sector. The paper begins by establishing a precise conceptual framework, defining public enterprises as general organizations established to manage various forms of economic activity under state supervision, while carefully distinguishing them from government agencies and public authorities in terms of administrative independence, legal personality, and operational flexibility. The study elaborates a detailed typology of public enterprise activities, classifying them into three main categories: enterprises engaged in comprehensive development across all economic sectors, single-sector development enterprises, and narrowly specialized enterprises focused on one branch of activity, drawing on comparative international experiences from Chile's CORFO and Turkey's Sümerbank. Regarding the administrative dimension, the paper reviews the foundations and key definitions of scientific management and identifies five core managerial functions essential to public enterprise effectiveness: planning, organizing, staffing, coordination, and control. Three specific functions are designated exclusively for supervisory public enterprises: planning and coordination, implementation oversight, and the provision of technical advisory services to subordinate units. In terms of organizational structure, the author proposes a comprehensive line-and-staff functional organizational framework comprising eight specialized departments — including project management, research and evaluation, planning and follow-up, financial and administrative affairs, accounts auditing, legal affairs, public relations, and board secretariat — with each department's jurisdiction defined with precision. The study concludes that the success of public enterprises is contingent upon organizational stability and the rigorous application of scientific management principles, away from the repeated legislative amendments that had undermined these institutions since their establishment in 1957.